Colonial Patriotism to “Mystical Chords of Memory”: The Halifax Celebrations and Commemorations of the Shannon-Chesapeake Battle - Mercer, Keith (Acadiensis, 2015)
Fought during the War of 1812, the Shannon-Chesapeake naval battle was one of the most important cultural events in Halifax’s history. The Shannon’s victory celebrations in 1813 sparked an unprecedented display of colonial patriotism and literature in the British North American context. This event remained at the forefront of public memory, history, art, and music throughout the 19th century. As personal connections to the battle faded at the turn of the 20th century, local authors such as Archibald MacMechan combined with historic sites organizations and the newly established Canadian Navy to keep its memory alive through commemorations and anniversaries